Structure-property relationship of phenylene-based self-assembled monolayers for record low work function of indium tin oxide - Benneckendorf, Frank S.; Hillebrandt, Sabina; Rohnacher, Valentina; Jänsch, Daniel; Freudenberg, Jan; Beck, Sebastian; Pucci, Annemarie; Bunz, Uwe H. F. (The journal of physical chemistry letters, 2018)
Studying the structure-property relations of tailored dipolar phenyl and biphenylphosphonic acids, we report self-assembled monolayers with a significant decrease in the work function (WF) of indium-tin oxide (ITO) electrodes. Whereas the strengths of the dipoles are varied through the different molecular lengths and the introduction of electron-withdrawing fluorine atoms, the surface energy is kept constant through the electron-donating N,N-dimethylamine head groups. The self-assembled monolayer formation and its modification of the electrodes are investigated via infrared reflection absorption spectroscopy, contact angle measurements, and photoelectron spectroscopy. The WF decrease in ITO correlates with increasing molecular dipoles. The lowest ever recorded WF of 3.7 eV is achieved with the fluorinated biphenylphosphonic acid.
Gesehen am 11.03.2020